Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 11 - Rational Expressions and Functions - 11-5 Solving Rational Equations - Practice and Problem-Solving Exercises - Page 683: 27


$m=-\frac{3}{2}, 4$

Work Step by Step

Given: $3(m+4)=2m(m-1)$ $3m+12=2m^2-2m$ $2m^2-2m-3m-12=0$ $2m^2-5m-12=0$ $2m^2+8m-3m-12=0$ $(2m+3)(m-4)=0$ Solutions are: $2m+3=0 \implies m=-\frac{3}{2}$, and $m-4=0 \implies m=4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.